2016
DOI: 10.1310/hpj5109-752
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Implementation of an Alcohol Withdrawal Protocol at a Single Institution

Abstract: Background There are varying dosing strategies for the administration of benzodiazepines in the setting of alcohol withdrawal. In October 2014, a symptom-based alcohol withdrawal protocol (AWP) using the Clinical Institute Withdrawal Assessment of Alcohol, Revised (CIWA-Ar) scale was implemented at one institution. Objective To evaluate the safety and efficacy of the AWP. Methods Retrospective chart review was completed, including patients receiving at least one dose of diazepam for alcohol withdrawal pre- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…We performed a calculation of statistical power a priori based on a minimally clinically significant finding of 24 hours difference in median duration of benzodiazepine use between both groups. A recent study has shown that institution of an AWS treatment protocol in medical inpatients led to a significant difference in treatment duration of approximately 30 hours 7 . We believe that given the high variability of the population being studied, the standard deviation would be approximately 48 hours.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…We performed a calculation of statistical power a priori based on a minimally clinically significant finding of 24 hours difference in median duration of benzodiazepine use between both groups. A recent study has shown that institution of an AWS treatment protocol in medical inpatients led to a significant difference in treatment duration of approximately 30 hours 7 . We believe that given the high variability of the population being studied, the standard deviation would be approximately 48 hours.…”
Section: Methodsmentioning
confidence: 88%
“…While numerous studies have demonstrated the effectiveness of such AWS protocols in decreasing morbidity associated with AWS on medical and surgical wards, 2‐6 many of these exclude patients with psychiatric comorbidities, and there are no published studies, to our knowledge, investigating the efficacy of AWS evaluation and treatment methods exclusively for psychiatric inpatients. One study evaluating the effects of implementation of a symptom‐triggered protocol included psychiatric inpatients in addition to medical patients 7 . Another study evaluating the impact of gabapentin in conjunction with benzodiazepines for management of AWS was conducted using psychiatric inpatients undergoing symptom‐triggered therapy, but did not evaluate the safety nor effectiveness of the symptom‐triggered protocol 8 …”
Section: Introductionmentioning
confidence: 99%
“…Prior studies in AWS management have established the superior effectiveness of symptom-triggered AWS protocols over fixed-dose tapering (or provider preference) in reducing AWS-related complications including DT, need for intubation, and escalation in care to an IMU or ICU. [14][15][16] Other studies have also demonstrated the effectiveness of symptom-driven approaches to decrease the length of hospitalization, 15,17,18 lower the required benzodiazepine exposure necessary to treat AWS, 7,12,15,[17][18][19][20][21][22][23][24][25][26][27][28] and reduce the duration of treatment with benzodiazepine sedation. 7,12,[22][23][24][25][26][27]29 Although there are other effective validated indices described in the literature, 29 the CIWA-ar remains one of the most widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term persistent exposure to alcohol results in altered central nervous system function such that abrupt cessation of alcohol use leads to a spectrum of symptoms ranging from mild tremor to seizures or delirium tremens (DT), a diagnosis associated with a 15%-20% mortality rate without appropriate medical care. 7 Furthermore, although the course of withdrawal can be mild, it has been estimated that 20% of patients in AWS will experience more serious manifestations meriting hospitalization for observation and treatment. 8 In addition, patients hospitalized for other medical or surgical reasons, and who experience symptoms of AWS, can have higher morbidity and mortality, and increased length of hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…One study found no reductions in LOS, total BZD use, or safety events 14 . Another study found reductions in the average cumulative BZD use but no improvement to LOS or safety 15 …”
mentioning
confidence: 99%